Rheological response of compressible SMCs under various deformation kinematics: Experimental aspects and simple modelling approach. (March 2022) - Ferré-Sentis, D.; Dumont, P.J.J.; Orgéas, L.; Martoïa, F.; Sager, M.
Abstract: Flow conditions during compression moulding of Sheet Moulding Compounds (SMCs) govern the microstructure and the resulting mechanical properties of composite parts. Low-density and high-fibre content SMCs were subjected to simple compression, œdometric compression and through-thickness shear loadings, using dedicated rheometers. Simple compression and œdometric compression experiments revealed the compaction behaviour of both types of SMCs. During simple compression experiments, the compaction of low-density SMCs was accompanied by in-plane elongational flow phenomena, whereas the high-fibre content SMCs exhibited compaction below a characteristic axial strain and elongation and shear above. Shear tests showed that shear stress did not vary over a wide range of shear strain while being accompanied by axial compression stress. Both SMCs exhibited a shear-thinning behaviour with compression viscosities that depended on the fibre volume fraction. Finally, a transversely isotropic tensorial model for SMCs seen as compressible materials was proposed. Its predictions are consistent with the experiments.